Optimizing The Use of Fermented Palm Kernel Cake in Feed by Giving Humic Acid in Drinking Water on Broiler Performance - Fajrona, Kadran; Ciptaan, Gita; Mirnawati (Andalasian Livestock, 2025)
This study aims to determine the dose of humic acid in drinking water to optimize the use of fermented palm kernel cake (FPKC) in broiler feed. The experimental design used was a completely randomized design (CRD) with 5 treatments (T1: 0% FPKC and 0% humic acid, T2: 25% FPKC + 100 ppm humic acid, T3: 25% FPKC + 200 ppm humic acid, T4: 30% FPKC + 100 ppm humic acid and T5: 30% FPKC + 200 ppm humic acid) and 4 replications. The variables observed were feed consumption, body weight gain, feed conversion, live weight, carcass percentage and abdominal fat percentage. The data obtained were analyzed by analysis of variance (ANOVA), if there was an effect between treatments it was continued with Duncan's multiple range test (DMRT). The results showed that the effect of humic acid in drinking water had no significant effect (P>0.05) on the T1, T2 and T3 treatments, but had a highly significant effect (P<0.01) on the T4 and T5 treatments. Giving humic acid in drinking water has not been able to optimize the use of FPKC up to 30%, but giving 100 ppm humic acid can optimize the use of FPKC as much as 25% in feed.